Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1994
DOI: 10.1016/0735-1097(94)90144-9
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin generation in human coronary arteries after percutaneous transluminal balloon angioplasty

Abstract: Markers of thrombin generation and activity can be collected safely and assayed accurately in heparinized blood withdrawn through an angioplasty catheter. Balloon dilation of coronary stenoses increases thrombin generation and activity within the coronary artery in a substantial subgroup of patients undergoing angioplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 27 publications
2
33
0
1
Order By: Relevance
“…This leads to the generation of large amounts of the serine protease thrombin through activation of the coagulation cascade by the tissue factor pathway (Marmur et al, 1994). By binding the subendothelial extracellular matrix, thrombin remains functionally active, localized, and protected from inactivation by circulating inhibitors (Schrör et al, 2010).…”
Section: (␣S)-n-[(1s)-3-amino-1-[[(phenylmethyl)-amino]carbonyl]propymentioning
confidence: 99%
“…This leads to the generation of large amounts of the serine protease thrombin through activation of the coagulation cascade by the tissue factor pathway (Marmur et al, 1994). By binding the subendothelial extracellular matrix, thrombin remains functionally active, localized, and protected from inactivation by circulating inhibitors (Schrör et al, 2010).…”
Section: (␣S)-n-[(1s)-3-amino-1-[[(phenylmethyl)-amino]carbonyl]propymentioning
confidence: 99%
“…1,2 Thrombin is generated in large amounts at the site of injury after balloon angioplasty and is amplified by formation of the prothrombinase complex both in humans and animals. [3][4][5] Exposure of tissue factor in the atherosclerotic plaque to flowing blood leads to increased thrombin generation, resulting in platelet-and fibrin-rich thrombus formation. 3,6,7 The important role of thrombin in generating acute platelet-rich thrombus and vascular healing after arterial injury is well documented.…”
mentioning
confidence: 99%
“…[3][4][5] Exposure of tissue factor in the atherosclerotic plaque to flowing blood leads to increased thrombin generation, resulting in platelet-and fibrin-rich thrombus formation. 3,6,7 The important role of thrombin in generating acute platelet-rich thrombus and vascular healing after arterial injury is well documented. 8 -11 Thrombin is also the most potent activator of platelets, and its expression is upregulated in smooth muscle cells after severe arterial injury.…”
mentioning
confidence: 99%
“…It is unknown which is the most reliable marker of thrombin generation after PCI. The serum F1+2 concentration exceeds the normal only in severe hypercoagulable states, 4,6) and Haude, et al 7) showed that the F1+2 concentration is the most specific and useful predictor of subacute stent thrombosis. FPA is very sensitive and indicates coagulation activity in real time because of its short 29.5 ± 6.9 § POBA = plain old balloon angioplasty; STENT = stenting; CB = cutting balloon angioplasty; CAG = coronary angiography; PAI-1 = plasminogen activator inhibitor-1.…”
Section: Discussionmentioning
confidence: 99%